Revitalizing Widosari Tourism Village: Enhancing User Experience and Service Delivery through Website Interface Redesign - Muhtahsin, Dian Amin; Irfan, Rahmatul (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
Tourism villages play an important role in the development and sustainability of a region by encouraging economic growth, cultural preservation, environmental preservation, and community development. Widosari Tourism Village is one of the tourist villages that attracts many visitors, as can be seen from the significant increase in traffic visiting the promotional website after being declared as a nominee in the Top 50 Indonesian Tourism Village Award 2022 event. However, the increase in traffic visiting the website was not matched by the website's carrying capacity. in providing services and conveying information to tourists. This has an impact on the lack of tour package sales in the Widosari Tourism Village. However, after redesigning the interface, drastic changes occurred, especially in the increase in sales of tour packages. This research was conducted to reveal and tell about the extent of the impact or benefits of a website redesign that is adapted to design principles as it is today compared to before the redesign was carried out. The method used in this research is descriptive qualitative research. In this research, the conclusion was obtained that after the website redesign was carried out, in terms of tourist reservation services, managers and tourists found it easier to communicate and connect, then the information on the website was easier for tourists to understand and capture. So, the presence of the Widosari Tourism Village promotional website functions as a means to facilitate tourism activities in the Widosari Tourism Village.